Pengaruh Harga, Kepercayaan, dan Promosi terhadap Keputusan Pembelian pada Pengguna E-commerce Tokopedia - Maria Sandra Daiman; Ima Kristina Yulita; Gregorius Hendra Poerwanto (EXERO : Journal of Research in Business and Economics, 2023)
This study aims to determine the effect of price, trust, and promotion on purchasing decisions of Tokopedia e-commerce users. The sampling technique used is purposive sampling. This study obtained data by distributing questionnaires via google form to 96 respondents. The test instruments used are validity and reliability tests. The data analysis technique used in this research is descriptive analysis, classical assumption test, multiple linear regression, F test and t test. Data processing using SPSS Statistics 23 Software. The results obtained from this study include 1) Price, trust, and promotion simultaneously affect purchasing decisions for e-commerce users of Tokopedia, 2) Price does not affect purchasing decisions on e-commerce users Tokopedia, 3) Trust has an effect on purchasing decisions for Tokopedia e-commerce users and 4) Promotion has an effect on purchasing decisions for Tokopedia e-commerce users.